PENDAPATAN DAN RESIKO USAHA PENGOLAHAN IKAN CAKALANG BANDA DI KECAMATAN BANDA - Willem Talakua (Journal Omni-Akuatika, 2014)
Constraints availability of raw materials and an increase in production costs faced by processors salted fish skipjack Banda (Katsuwonus pelamis) would pose a high risk of doing business, the possibility of adverse conditions. This study therefore aimed to determine the risk level of income and business processing cakalang banda in the district of Banda. Determination of the location of the purposive, and collection of data through observation and interviews as well as secondary data. Through the analysis of income and business risk analysis, the results showed that the processing business cakalang Banda in the  district  of  Banda  classified as  family businesses with  average income earned during  the year amounting to Rp 950.815/year with a very small level of business risk of the loss, which value of the coefficient of variation (CV) <0.5 and lower profits limit (L)> 0 which means that the tuna processing Banda will not experience any loss of production process.Keywords : Income, Business Risk, Banda Skipjack Fish.